Moderating effect of employee's commitment to change on the relationship between leadership styles and employee's readiness to change in Yemen - Al-Douis, Gamal Abdullah Ali (2019)
Change in the public sector is one of the main concerns due to its critical role in enhancing the public sector which consequently contributes to the development of the economy and society. Yemen as a least developed country, its employees of public sector were unable to implement the changes planned. Besides, there is a gap in the literature in terms of examining the influencing and moderating factors that could affect the employee’s readiness to change. The aim of this thesis is to examine the effects of transformational leadership (TFL) style, transactional leadership (TAL) style and employee’s commitment towards change (ECC) on the employee’s readiness to change (ERC). The thesis also examines the moderating effect of ECC on the relationship between the two leadership styles (TFL and TAL) with ERC. The thesis utilizes Lewin's model and Social Exchange Theory (SET) as guiding theories and employs cross-sectional survey. The questionnaires were administered to collect data from the employees of the public sector in Yemen. Out of 768 questionnaires distributed through a self-administered approach, 387 usable responses were used for the analysis. By using Partial Least Square-Structural Equation Modeling, the findings show significant effects of TFL and ECC on the ERC. Furthermore, the findings show that TAL is not significantly related to ERC among the employees of the public sector in Yemen. Additionally, the findings reveal that ECC is a significant moderator on the relationship between TAL and ERC. These findings provide theoretical and practical implications. It contributes towards the body of knowledge of how employees are ready to changes in the public sectors of a least-developed country. It also provides significant insights in explaining a roadmap that help in understanding the most influential factors on employee’s readiness to change in a least developed country namely Yemen.